MODEL KOMUNIKASI PENANGANAN KELUHAN TENANT DI APARTEMEN PARAMA - Dienda Audra Syari; Ahmad Toni (Universitas Baturaja, 2021)
This study aims to determine the implementation of tenant complaint handling at Parama Apartments. The procedures for handling tenant complaints at Parama Apartments are as follows: (a) Tenant Relations receives complaints; (b) Tenant Relations records complaints on the Complaint Request (CR) form; (c) Provide CR form sheets to the relevant Department; (d) Followed up by other Departments; (e) Supervisor conducts field checks; (f) the Chief fills in the Work Order (WO) form; (g) the relevant department undertakes remedial work to eliminate complaints; (h) The relevant department completes and signs the CR form on the action line and asks for acknowledgment of work results from tenants; (i) Tenant Relation receives CR form from the relevant department; (j) Tenant Relations records in the complaint list; and (k) Tenant Relations makes monthly reports; and the communication model for handling tenant complaints, including conducting regular tenant satisfaction surveys organized by the Parama Apartment Owners and Occupants Association (PPRSHAP).